Whole-genome sequence analysis for evaluating the safety and probiotic potential of Lactiplantibacillus pentosus 9D3, a gamma-aminobutyric acid (GABA)-producing strain isolated from Thai pickled weed - Raethong, Nachon; Santivarangkna, Chalat; Visessanguan, Wonnop; Santiyanont, Pannita; Mhuantong, Wuttichai; Chokesajjawatee, Nipa (Frontiers in Microbiology, 2022)
Lactiplantibacillus pentosus 9D3, a prominent gamma-aminobutyric acid (GABA)-producing bacteria isolated from Thai pickled weed was characterized for its safety and probiotic properties via whole-genome analysis and in vitro testing. The whole-genome sequence (WGS) of L. pentosus 9D3 was determined using a hybrid-sequencing approach, combining PacBio and Illumina technologies. A 3.81-Mbp genome of L. pentosus 9D3 consisting of one 3.65-Mbp chromosome and six plasmids (1.9-71.9 Kbp) was identified with an estimated GC content of 46.09% and 3,456 predicted genes. The strain was confirmed to be Lactiplantibacillus pentosus according to the high average nucleotide identity (ANI) value of >95% and digital DNA-DNA hybridization (dDDH) scores of >70% to the L. pentosus type strain. Comparative genome analysis with other L. pentosus strains showed that the GABA-producing capability was specific to the strain 9D3. Genes related to GABA biosynthesis and transport were identified on a plasmid, pLPE-70K, indicating the acquired nature of this property. The safety of L. pentosus 9D3 was demonstrated through the lack of genes related to the production of toxins, biogenic amines, and antimicrobial drugs. Although the strain exhibited resistance to ampicillin and chloramphenicol, none of the antimicrobial resistance (AMR) genes were associated with mobile elements, i.e., plasmids and prophages. Therefore, the strain is considered to have low risk of transferring the AMR genes to other, potentially pathogenic bacteria. In addition, L. pentosus 9D3 showed good survivability in the gastrointestinal (GI) tract environment and was able to adhere to the intestinal cell in vitro. Therefore, L. pentosus 9D3 is concluded to be safe, with the potential to be used as a probiotic, exerting its health benefit through GABA production in the food system. The GABA-producing capability of the strain in vivo is the subject of further investigation.